Heterothermy use in winter is associated with reduced litter size during following breeding season - Boratyński, Jan S.; Iwińska, Karolina; Zub, Karol (Frontiers in Ecology and Evolution, 2024)
Heterothermy is considered to be the most effective energy-saving strategy improving survival under natural conditions. Interspecific studies suggest that this strategy is also associated with reduced reproductive output. Yet little is known about the reproductive consequences of heterothermy use at the intraspecific level and thus its repercussions for microevolutionary processes. Moreover, as yet no study has aimed to test if litter size and juvenile mass are affected by torpor use in wild captured animals under undemanding laboratory conditions. Here we tested the hypothesis that intraspecific variation in heterothermy use is associated with different reproductive successes, being the result of the evolution of distinct life histories. We predicted that heterothermy use in winter negatively correlates with litter size and juvenile body mass during the subsequent breeding season. To test this prediction, we used yellow-necked mice from a population in which individuals consistently differ in their use of heterothermy in winter. We measured body size (head width) and body mass, basal metabolic rate, as well as metabolism and body temperature during fasting-induced torpor in wild caught mice in winter. Phenotyped mice were bred in the subsequent summer selectively -males and females with similar heterothermy characteristics were paired, the most to the least heterothermic. Dam body size, but not basal metabolism, was positively correlated with litter size (but not juvenile mass).However, when accounting for this relationship, litter size was negatively while juvenile mass was positively correlated with the average heterothermy use of a given couple. Our study indicates that heterothermy correlates with specific life-history strategies arising from a fundamental evolutionary trade-off between survival and reproduction.